1985
DOI: 10.1002/hep.1840050410
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Controlled Trial of Chronic Esophageal Variceal Sclerotherapy

Abstract: The results of a prospective, randomized controlled trial of chronic esophageal variceal sclerotherapy conducted over a 38-month period are presented. One-hundred twenty patients were randomized following variceal bleeding, 63 to esophageal variceal sclerotherapy and 57 to control. Mean follow-up was similar in both groups (esophageal variceal sclerotherapy, 12.5 +/- 8.8 months; control, 14.9 +/- 6.6 months). Twenty-one percent of the patients in each group were lost to follow-up. Esophageal variceal sclerothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…Endoscopic injection sclerotherapy (EIS) has been well documented as a valuable tool to help control acute variceal bleeding, to prevent recurrent bleeding, and perhaps to improve survival. [1][2][3][4] However, it may be associated with substantial complications. 5 Endoscopic variceal ligation (EVL) has emerged in recent years as a new tool in the management of bleeding esophageal varices.…”
mentioning
confidence: 99%
“…Endoscopic injection sclerotherapy (EIS) has been well documented as a valuable tool to help control acute variceal bleeding, to prevent recurrent bleeding, and perhaps to improve survival. [1][2][3][4] However, it may be associated with substantial complications. 5 Endoscopic variceal ligation (EVL) has emerged in recent years as a new tool in the management of bleeding esophageal varices.…”
mentioning
confidence: 99%
“…1 rate could be lowered [3][4][5][6][7][8] and survival prolonged. 4,6,9,10 Studies Patients who have bled from varices remain at risk with rubber band ligation have shown that in addition to for rebleeding.…”
mentioning
confidence: 99%
“…90-3.86). In general, nonselective shunt surgery was associated with significantly lower rebleeding rates, but the incidence of hepatic encephalopathy was significantly higher [89][90][91]. The mortality rates between the two groups were similar.…”
Section: Endoscopic Therapy Versus Surgerymentioning
confidence: 58%